Is the primary AZFc duplication a potential risk for male infertility?: A systematic review and meta‐analysis. (2nd May 2020) - Xie, Shengyu; Zhang, Yangwei; Yang, Yuan
Abstract: Background: Numerous studies have been performed to investigate the association between the primary AZFc duplication and male infertility risk; however, the sample sizes have been small and the results have been controversial. A meta‐analysis was performed to assess these associations. Methods: A systematic search was conducted to identify all relevant studies from the PubMed, Web of Science, Medline, CNKI, and Wanfang databases up to October 22, 2019. The odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to assess the strength of associations. All of the statistical analyses were conducted by using RevMan 5.3. Results: Eleven studies were identified that involved 3140 infertile men and 2280 fertile men. Overall, there was a statistically significant association between the primary AZFc duplication and male infertility (OR = 1.66, 95% CI = 1.29‐2.14, P < .0001). In the subgroup analysis by ethnic group, a statistically significant association between the primary AZFc duplication and male infertility was observed in Asian men (OR = 2.26, 95% CI = 1.64‐3.12, P < .00001), but not in European men (OR = 0.90, 95% CI = 0.59‐1.38, P = .64). For subtypes of the primary AZFc duplication, a statistically significant association was observed between the gr/gr duplication‐only (OR = 2.71, 95% CI = 1.38‐5.32, P = .004) and infertility in Asian men. Asian men with the primary AZFc duplication resulting in more than four DAZ genes were found to be at an increased risk for infertility (OR = 2.70, 95% CI = 1.49‐4.89, P = .001). Conclusion: Our meta‐analysis provides an unprecedented illustration of how the association between the primary AZFc duplication and male infertility may be dependent on ethnicity or geographic location. Furthermore, gr/gr duplication or increased DAZ copy number can be detrimental to spermatogenesis in Asian men.